2019
DOI: 10.3920/jiff2018.0021
|View full text |Cite
|
Sign up to set email alerts
|

The house cricket (Acheta domesticus) as a novel food: a risk profile

Abstract: Novel foods represent sustainable alternatives to traditional farming and conventional foodstuffs. The house cricket (Acheta domesticus) is considered as one of the most promising reared insects due to their attractive nutritional profile and lower feed conversion ratio compared to other animals. However, putative health hazards associated with consumption of crickets have previously not been investigated. The present study assesses the risks of A. domesticus reared in closed systems controlled by the implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 112 publications
0
70
0
2
Order By: Relevance
“…However, due the huge diversity within the insects’ world, there is a need to target insect species relevant for European consumers specifically. Therefore, a specific risk profile for the consumption of A. domesticus reared in controlled conditions has been developed (Fernandez‐Cassi et al., submitted).…”
Section: Introductionmentioning
confidence: 99%
“…However, due the huge diversity within the insects’ world, there is a need to target insect species relevant for European consumers specifically. Therefore, a specific risk profile for the consumption of A. domesticus reared in controlled conditions has been developed (Fernandez‐Cassi et al., submitted).…”
Section: Introductionmentioning
confidence: 99%
“…Like parasites, there are many entomopathogenic viruses specific for invertebrates that cause Animal Health problems, but their presence and virulence in vertebrates have never been described [30]. The most well-known are the Densoviruses (AdDV) and the Cricket Paralysis Virus (CrPV), with the latest to cause particularly high mortality rates for A. domesticus populations [19]. These viruses are a severe problem in mass rearing for the production of food for humans or animals [12].…”
Section: Virusesmentioning
confidence: 99%
“…Nevertheless, it has been demonstrated that some insect species can act as mechanical vectors of prions that are present in the rearing substrate, as highlighted for scrapie in sheeps [34]. Reference [19] summarized studies that report the high stability of prions in the environment, and the prions' ability to maintain their infectivity for long timespan in soil and water. Use of substrates of non-human and non-ruminant origin [12], as well as control of the substrate's quality and feed quality [19] could act as preventive measures to avoid occurrence of prions in the edible insects.…”
Section: Prionsmentioning
confidence: 99%
See 2 more Smart Citations